Осознание виртуальности реальности - Роговец, В. Е. (ХНУРЕ, 2020)
With the development of technology, the issue of virtual reality is becoming increasingly relevant and popular in philosophy. This work aims to outline the main theses of such a moment as distinction between virtual and actual realities.
Keywords: философия; осознание виртуальности реальности